2014
DOI: 10.1111/etap.12040
|View full text |Cite
|
Sign up to set email alerts
|

Motives and Outcomes in Family Business Succession Planning

Abstract: The family business succession planning literature routinely assumes two main motives on the part of incumbents: family business continuity across generations and family harmony. The cross–tabulation of these motives produces a typology consisting of four distinct combinations of motives for succession planning. In turn, these combinations suggest four outcomes of succession planning, framed as institutionalization, implosion, imposition, and individualization. The first two outcomes—institutionalization and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 33 publications
0
118
0
3
Order By: Relevance
“…The important role of these program managers can also be perceived as their greatest weakness, as it is uncertain the direction such programs will take when these manager are not in their roles anymore. Succession planning was never discussed during this study, so retirement or withdrawal of entrepreneurial and driving leaders is likely to have a severe negative effect on program performance, similar to the negative effects of a lack of succession planning in private businesses [77,78].…”
Section: Comparison Of Programsmentioning
confidence: 98%
“…The important role of these program managers can also be perceived as their greatest weakness, as it is uncertain the direction such programs will take when these manager are not in their roles anymore. Succession planning was never discussed during this study, so retirement or withdrawal of entrepreneurial and driving leaders is likely to have a severe negative effect on program performance, similar to the negative effects of a lack of succession planning in private businesses [77,78].…”
Section: Comparison Of Programsmentioning
confidence: 98%
“…Successful succession is reported to be critical to securing the family business across generations and to ensuring family harmony (Gilding, Gregory and Cosson, 2013). Hence, succession is a key topic in family business research (Chrisman, Chua and Sharma, 1998;De Massis, Chua and Chrisman, 2008;Gilding et al, 2013;Helin and Jabri, 2015;Lam, 2011;Litz, Pearson and Litchfield, 2012;Sharma, Chrisman and Chua, 2003;Zahra and Sharma, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that only 30% of family companies survive into the second generation and only 15% into the third. Proper succession planning is essential for a successful transition (Gilding, Gregory, & Cosson, 2015;Hjorth & Dawson, 2016;Morris, Williams, & Nel, 1996).…”
Section: The Challenges Of a Family-run Businessmentioning
confidence: 99%